Pengaruh Struktur Modal, Kebijakan Dividen Dan Inflasi Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Sub Sektor Tekstil Dan Garmen Di Bei Pada Tahun 2016-2018) - Ayu Trisnawati; Ronny Malavia Mardani; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThe purpose of this research was to specify impact of Capital Fabric, Dividend Policy, and Inflation on Company Values (study on textile and garment sub-sector companies listed on the IDX in the year of 2016-2018) The population using this research were manufacturing companies in textile and garment sub-sector listed on the Indonesia Stock Exchange in 2016-2018. The sample used in research is a technique purposive sampling. Corporation that enter the research criteria consist of 17 companies over a 3 year period. The data collection method employed in research is documentations the monetary statements of manufacturing companies in the textile and garment sub-sector listed on the IDX. While the analysis of employed is multiple linear regression by testing the hypothesis using the T test. The output of the research explain the variable Capital Structure has a positive and significant influence on Company Value. Dividend policy has a positive and significant impact on Company denomination. While inflation has no significant effect on firm denomination. Keywords: Capital Structure, Dividend Policy, Inflation and Firm Value